Songs in Action - Gelineau, R. Phyllis (Parker Pub. Co., 1988)
Keywords: Instruction and study; School music; dept.edu; faculty_collection

The development of an understanding of balance and the effect of training via stop-action video☆ - Fosnot, Catherine Twomey; Forman, George E; Edwards, Carolyn P; Goldhaber, Jeanne (Journal of Applied Developmental Psychology, 1988)
Children's rule-governed, scientific reasoning in relation to the physical principles involved in balance has been studied by many, for example, Inhelder and Piaget (1958), Karmiloff-Smith and Inhelder (1974), as well as Siegler (1978). Although Siegler criticized the Genevan research on both methodological and conceptual grounds, his work can be criticized for being narrow in scope thus making his data a result of his task and design, rather than a true representation of the rules children employ naturally as they develop an understanding of balance. The work described herein is an attempt to integrate the methodologies of the Piagetian School and Siegler by making use of current video technology to naturalistically assess children's rule-governed behaviors but to also empirically validate them. The first part of this study (N=128, ages 4-9 years) used video to microanalytically assess the strategies children used as they attempted to balance a set of symmetrical, asymmetrical, and weighted blocks on a fulcrum. After validating on ordinal progression of strategies, the study used stop-action video feedback, in a predict-consequence paradigm, to focus reflection on (a) the action of the block, (b) the placement of the block, and (c) the episode in general. A two-way interaction between entering level and type of video feedback was significant. The results are interpreted in terms of Piaget's theory of equilibration suggesting that reflection and cognitive conflict can improve understanding if the child assimilates the feedback to the confirmation or refutation of an initial assimilatory scheme regarding balance. © 1988.
Keywords: dept.edu